INTENSIFIKASI LAHAN PERTANIAN MENGGUNAKAN AIR BAWAH TANAH (RENCANA PROYEK PERCONTOHAN DI SUBAK SAYEHAN JASRI KARANGASEM - Simpen, I N.; Ratini, N. N.; Wibawa, I M. S.; Suryatika, I. B. M. (Buletin Udayana Mengabdi, 2017)
One way that can be done in the intensification of agricultural land is irrigate with groundwater during the dry season or when the river water is not there. In Subak Sayehan Jasri Karangasem going to do a pilot project intensification of agricultural land use underground water. Objective of community service activities is to determine the point of drilling to obtain underground water is most effective. Drilling point sought by the geoelectric method. The results have been obtained drilling point, at a distance of 115-126 m from the side of the road, estimated to a depth of 13 m has been found water, recommended drilling to a depth of 25 m.